Role of Pannexin-1-P2X7R signaling on cell death and pro-inflammatory mediator expression induced by Clostridioides difficile toxins in enteric glia - Loureiro, Andrea V.; Moura-Neto, Lauro I.; Martins, Conceição S.; Silva, Pedro I. M.; Lopes, Matheus B.S.; Leitão, Renata F. C.; Coelho-Aguiar, Juliana M.; Moura-Neto, Vivaldo; Warren, Cirle A.; Costa, Deiziane V.S.; Brito, Gerly A. C. (Frontiers in Immunology, 2022)
Clostridioides difficile (C. difficile) produces toxins A (TcdA) and B (TcdB), both associated with intestinal damage and diarrhea. Pannexin-1 (Panx1) channels allows the passage of messenger molecules, such as ATP, which in turn activate the P2X7 receptors (P2X7R) that regulate inflammation and cell death in inflammatory bowel diseases. The aim of this study was to verify the effect of C. difficile infection (CDI) in the expression of Panx1 and P2X7R in intestinal tissues of mice, as well as their role in cell death and IL-6 expression induced by TcdA and TcdB in enteric glial cells (EGCs). Male C57BL/6 mice (8 weeks of age) were infected with C. difficile VPI10463, and the control group received only vehicle per gavage. After three days post-infection (p.i.), cecum and colon samples were collected to evaluate the expression of Panx1 by immunohistochemistry. In vitro, EGCs (PK060399egfr) were challenged with TcdA or TcdB, in the presence or absence of the Panx1 inhibitor (10Panx trifluoroacetate) or P2X7R antagonist (A438079), and Panx1 and P2X7R expression, caspase-3/7 activity and phosphatidylserine binding to annexin-V, as well as IL-6 expression were assessed. CDI increased the levels of Panx1 in cecum and colon of mice compared to the control group. Panx1 inhibitor decreased caspase-3/7 activity and phosphatidylserine-annexin-V binding, but not IL-6 gene expression in TcdA and TcdB-challenged EGCs. P2X7 receptor antagonist accentually reduced caspase-3/7 activity, phosphatidylserine-annexin-V binding, and IL-6 gene expression in TcdA and TcdB-challenged EGCs. In conclusion, Panx1 is increased during CDI and plays an important role in the effects of C. difficile toxins in EGCs, participating in cell death induced by both toxins by promoting caspase-3/7 activation via P2X7R, which is also involved in IL-6 expression induced by both toxins.